Quality management and improvement for geothermal energy projects using the platform-based tool development technology − ZWERG. (January 2018) - Holbein, Benedict; Dietze, Stefan; Hurst, Franziska; Isele, Jörg; Spatafora, Luigi; Wiegel, Friedrich; Hagenmeyer, Veit
Highlights: An approach for modular platform based downhole tool development for harsh conditions is presented. Advantages in terms of development time, quality and reusability of results are demonstrated. Engineering solutions for pressure and corrosion resistant housing, heat management and data transfer are provided. The platform is usable as basis for a wide range of downhole tools for different applications. Abstract: Operations in deep geothermal boreholes are a technical challenge due to harsh conditions such as high pressures, high temperatures, limited space and corrosive thermal water. Therefore the development of tools for inspection, investigation and maintenance for geothermal applications is a challenging and expensive task. In consequence the operations in most cases are limited to simple measurements of pressure (p), temperature (T) and diameter (caliper). Other restrictions are waving of real-time data transfer and a limitation of operation depths at above the open-hole. The approach of ZWERG uses know-how from other industrial sectors for a modular design of downhole tools based on a system platform. This way it allows creating reproducible and reusable solutions for the main technical challenges: housing, sealing, compact interior design, heat management and data processing. It is supposed to build the basis for more widespread and more complex applications in deep boreholes and to support an economic development of new tools. Reliable modular platform solutions for basic challenges support an enhanced quality management for geothermal systems which profits from suitable tools for measurement, inspection, sample recovery, maintenance and repair that can be used all the way from the surface to the open hole.